JDBC practical guide for Java programmers - Speegle, Gregory D. (Gregory David) (San Francisco : MK/Morgan Kaufmann Publishers, 2002)
JDBC: Practical Guide for Java Programmers is the quickest way to gain the skills required for connecting your Java application to a SQL database. Practical, tutorial-based coverage keeps you focused on the essential tasks and techniques, and incisive explanations cement your understanding of the API features you'll use again and again. No other resource presents so concisely or so effectively the exact material you need to get up and running with JDBC right away. * Provides tutorial-based instruction in key JDBC techniques, complemented by example code. * Centered around an incrementally developed example of a three-tiered application for a video rental e-commerce site. * Designed to help you tackle standard JDBC tasks: connecting your database to the Internet, displaying query results, using stored procedures, updating the database, storing metadata, carrying out transactions, working with binary large objects, implementing security, and more. * Via the companion Web site, provides code for the examples, tools for loading the example database, links to useful JDBC sites, and a forum in which to interact with other readers.
1 -- Introduction to JDBC -- 2 -- Presenting Information to Users -- 3 -- Querying the Database -- 4 -- Updating the Database -- 5 -- Advanced JDBC Topics -- 6 -- An eCommerce Example -- 7 -- How to Stay Current with JDBC -- 8 -- Appendix.
Includes bibliographical references (p. 107) and index.
Keywords: Java (Computer program language).; Database management -- Computer programs; Application program interfaces (Computer software); Electronic books